Analytical review on influence of Krodha (Anger) on Agni - A Contemporary study (AYUSHDHARA, 2022)
Agni is the supreme entity residing in the living being responsible for digestion of Ahar dravya, Jatharagni is the principle Agni among all categories of Agni, it should be suitability maintained. Ayurveda suggests that there are number of factors like Krodha, Shoka, Chinta, Bhaya etc. Manas bhava affects the normal function of Agni apart from Doshik influence. In Ayurveda Ati, Heen and Mithya yoga of Asatmendriyasamyoga, Pradnyaparadha and Parinama are the main etiological factors for anger. Objective: This study attempts to understand effect of Krodha on Agni with supportive classical and contemporary view. Data source: The literary study has been conducted through various ancient text like- Charak samhita, Sushruta Samhita, Astang Hridayam and other Ayurveda texts. Various websites were also referred in this context. Discussion and Result: Pitta-Vata Vriddhi occurring on Krodha can be co-related to activation of sympathetic Nervous system. Agni dushti and Saman Vayu dushti that occurs in Krodha, can be understood as disturbance in enzymatic activities and motility of GIT. So, Krodha is the reason for impaired digestion of food and generation of different GIT disorders. Conclusion: This analytical study suggests that there is direct relationship of status of Manas (mind) and Agni (digestive fire).